UPAYA PEMERINTAH DALAM MEMBERIKAN INSENTIF RESMI UNTUK KOTA YANG LEBIH BERSIH - Syah Amin Albadry; Darmawanto; Sasmita Rusnaini; Ariyanto.M; Hamirul (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Economic life in this case is the income of an employee is important for sustainable life, including janitors, this article aims to determine the efforts of local governments in providing incentives. The research method used was descriptive and qualitative approach with data collection techniques used by interviews with 8 informants. Research Results Government efforts in providing incentives for city cleaners already exist, although it cannot be given more adequately to all janitors of the Bungo City City Market and Hygiene Management Office. In the government’s efforts to provide incentives for city cleaners, there are still obstacles from the Bungo District Market and Hygiene Management Office, namely the provision of inadequate budgets depending on the state’s financial situation. Efforts are being made to overcome government barriers in the provision of Insenitf city cleaning officers, namely by providing an adequate budget by including the proposed budget to the Regional Budget each year